2018
DOI: 10.1371/journal.pone.0191452
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profiling of microRNAs in the human embryonic inner ear

Abstract: Due to the extreme inaccessibility of fetal human inner ear tissue, defining of the microRNAs (miRNAs) that regulate development of the inner ear has relied on animal tissue. In the present study, we performed the first miRNA sequencing of otic precursors in human specimens. Using HTG miRNA Whole Transcriptome assays, we examined miRNA expression in the cochleovestibular ganglion (CVG), neural crest (NC), and otic vesicle (OV) from paraffin embedded (FFPE) human specimens in the Carnegie developmental stages 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…miRNA molecules are conserved throughout multiple species, have been identified in tissue and fluids throughout the body, and are known to play a significant role in various pathologies including cancer and other neurodegenerative diseases ( 25 , 26 ). miRNAs have also been shown to play a key role in inner ear development and show distinct expression patterns in patients with hearing loss compared to healthy controls, making them an intriguing biomarker ( 27 30 ). In previous work, we preliminary established Meniere's disease could be diagnosed based on perilymph miRNA profile alone, further validating miRNAs as a potential biomarker either through the perilymph or serum of patients ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA molecules are conserved throughout multiple species, have been identified in tissue and fluids throughout the body, and are known to play a significant role in various pathologies including cancer and other neurodegenerative diseases ( 25 , 26 ). miRNAs have also been shown to play a key role in inner ear development and show distinct expression patterns in patients with hearing loss compared to healthy controls, making them an intriguing biomarker ( 27 30 ). In previous work, we preliminary established Meniere's disease could be diagnosed based on perilymph miRNA profile alone, further validating miRNAs as a potential biomarker either through the perilymph or serum of patients ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because miRNA play a critical role in cell gene expression, miRNA activity has been increasingly recognized as a critical component to many disease states making them a promising biomarker 5,23 . Interestingly, miRNA profiles have shown unique expression patterns to different diseases states, from heart failure 24 to individual cancers 7 (colon 2527 , ovarian 28 , and clear cell carcinoma 29 ), neurodegenerative diseases 4 , different cell types 30 , and play an integral role embryonic development 8 . Pertinent to hearing loss, miRNA have shown to be a promising biomarker and diagnostic marker for otherwise difficult to diagnose neurodegenerative diseases such as Alzheimer’s and Parkinsons 4,5,31 .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are 19–23 base pair single stranded RNA sequences that regulate post translational gene expression 3 . These molecules have been identified in all body fluids and are recognized for their promising role as a diagnostic and prognostic marker for neurodegenerative diseases such as Alzheimer’s and various cancers 48 . We recently demonstrated that miRNA profiling within the inner ear is a feasible methodology and can potentially offer insight into what is occurring on a cellular and molecular level in various inner ear pathologies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Negative control probes were used as quality control to evaluate baseline performance, as previously described by Chandly and colleagues. [17] Briefly, the mean of negative probes for each sample was calculated, and the difference between negative control average and the mean of all negative control probes was obtained (Δ mean ). Those samples with a Δ mean outside the bounds of +/-2 standard deviation were excluded from the study.…”
Section: Data Filtering and Normalizationmentioning
confidence: 99%